2017
DOI: 10.1016/j.maturitas.2017.03.317
|View full text |Cite
|
Sign up to set email alerts
|

Wearables for independent living in older adults: Gait and falls

Abstract: Solutions are needed to satisfy care demands of older adults to live independently. Wearable technology (wearables) are one approach to offer a viable means for ubiquitous, sustainable and scalable monitoring in habitual free-living environments. Gait has been presented as a relevant (bio) marker in ageing and pathological studies, with objective assessment achievable by inertial-based wearables. Commercial wearables have struggled to provide accurate analytics and have been limited by non-clinically oriented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(49 citation statements)
references
References 146 publications
2
47
0
Order By: Relevance
“…The inclusion of a large sample -415 residents from 28 long-term care facilities and with varying levels of cognitive impairment -may have contributed to the higher rate of non-adherence we observed. Our findings and experiences during the study highlight the challenge of using wearable technology with cognitively impaired individuals and supports, more broadly, the need for more work in this area, particularly regarding practical issues such as device size, placement, and comfort [31].…”
Section: Discussionsupporting
confidence: 57%
“…The inclusion of a large sample -415 residents from 28 long-term care facilities and with varying levels of cognitive impairment -may have contributed to the higher rate of non-adherence we observed. Our findings and experiences during the study highlight the challenge of using wearable technology with cognitively impaired individuals and supports, more broadly, the need for more work in this area, particularly regarding practical issues such as device size, placement, and comfort [31].…”
Section: Discussionsupporting
confidence: 57%
“…33 Consequently, monitoring with sensors may increase timely referral to falls prevention programs, aiming to decrease the impact of falls on daily life and increase independence. 34 This potential of sensors becomes more important when considering the higher number of falls in participants with PD resulting in emergency transport that was observed in our study. Future research focusing on refining algorithms for fall detection, fall prediction, and fall risk analysis in daily living should explore the added value of tri-axial gyroscopes and/or tri-axial magnetometers.…”
Section: Discussionmentioning
confidence: 71%
“…Moreover, wearable sensors have potential to identify patients with a high risk of falling . Consequently, monitoring with sensors may increase timely referral to falls prevention programs, aiming to decrease the impact of falls on daily life and increase independence . This potential of sensors becomes more important when considering the higher number of falls in participants with PD resulting in emergency transport that was observed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Among the several devices considered to this purpose, it has been reported that wearable motion detectors are the most promising technology enabling an automatic, continuous and long-term assessment of subjects in free-living environments. This topic is so current that a search on ‘wearable sensors for elderly people’ on Google Scholar, listed over 1800 results since 2017 including [276,277,278]. …”
Section: Resultsmentioning
confidence: 99%